Experimental Trypanosoma evansi infection in donkeys: hematological, biochemical and histopathological changes - Cadioli, Fabiano Antonio [UNESP]; Marques, L.C. [UNESP]; Machado, R.Z. [UNESP]; Alessi, A.C. [UNESP]; Aquino, L.P.C.T. [UNESP]; Barnabé, P A. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2006)
Cinco jumentos, adultos foram infectados experimentalmente com cepa brasileira de Trypanosoma evansi, isolada de um cão naturalmente infectado, com o intuito de observar as alterações hematológicas, bioquímicas e histopatológicas durante a evolução da enfermidade. O curso da infecção experimental foi de 145 dias. Análise hematológica dos jumentos infectados revelou declínio nos valores de hemoglobina, hematócrito e contagem total de eritrócitos. Notou-se anemia após sucessivos picos de parasitemia. Análise bioquímica indicou aumento dos níveis de índice ictérico, globulinas séricas e diminuição dos valores séricos de albumina e glicose. Todos os jumentos infectados apresentaram aumento do baço e de sua polpa branca, aumento de linfonodos mediastínicos e congestão pulmonar. Meningoencefalite foi o principal achado histopatológico. em algumas áreas do pedículo cerebelar foram observadas desmielinização, além de vacuolização do neurópilo. O estudo mostrou que jumentos infectados com a cepa brasileira do T. evansi desenvolveram doença crônica.

Five adult donkeys were experimentally infected with Brazilian strain of Trypanosoma evansi originally isolated from a naturally infected dog to study the hematological biochemical and histopathological alterations during the evolution of the disease. The course of the experimental infection was followed up to 145 days. Hematological analyses of the infected donkeys revealed a marked decline in hemoglobin, packed-cell volume, and erythrocyte count. Anemia was observed after successive peaks of parasitemia. Biochemical analyses showed increased levels of icterus index, serum globulins and decreased serum albumin and glucose values. All infected donkeys revealed enlargement of spleen and its white pulp, enlargement of mediastinal lymph nodes and lungs congestion. The main histopathological features consisted of meningoencephalitis. Demyelination in some areas of the cerebellum pediculus and neuropil vacuolization were observed. This study showed that donkeys infected with a Brazilian strain of T. evansi developed a chronic disease.
Infecção experimental em jumentos com Trypanosoma evansi: alterações hematológicas, bioquímicas e histopatológicas
Keywords: Donkey; Experimental infection; Trypanosoma evansi; Trypanosomiasis; jumento; Infecção experimental; Trypanosoma evansi; tripanosomíase